"(2x+1)(x+1)y''(x)+2xy'(x)-2y=(2x+1)^2"
Ordinary differential equation classification: second-order linear ordinart differential equation.
1-step: Substitute "-2= \\tfrac{d}{dx}\t(2x) - \\tfrac{d^2}{dx}((x+1)(2x+1)):"
"\\tfrac{d^2 y(x)}{dx^2}\t(x+1)(2x+1)+2x \\tfrac{dy(x)}{dx}+( \\tfrac{d}{dx}(2x)- \\tfrac{d^2}{dx^2}((x+1)(2x+1)))y(x) = (2x +1)^2"
2-step: Expand
"\\tfrac{d^2 y(x)}{dx^2}(x+1)(2x+1)+2x\\tfrac{dy(x)}{dx}+\\tfrac{d}{dx}(2x)y(x)-\\tfrac{d^2}{dx^2}((x+1)(2x+1))y(x)=(2x+1)^2"
3-step: Add and subtract "\\tfrac{dy(x)}{dx}\\tfrac{d}{dx}((x+1)(2x+1))" to the left hand sinde:
"\\tfrac{dy(x)}{dx}\\tfrac{d}{dx}((x+1)(2x+1))+\\tfrac{d^2y(x)}{dx^2}(x+1)(2x+1)+2x\\tfrac{dy(x)}{dx}+\\tfrac{d}{dx}(2x)y(x)-\\tfrac{dy(x)}{dx}\\tfrac{d}{dx}((x+1)(2x+1))-\\tfrac{d^2}{dx^2}((x+1)(2x+1))y(x)=(2x+1)^2"
4-step: Apply the reverse product rule "f\\tfrac{dg}{dx}+g\\tfrac{df}{dx}=\\tfrac{d}{dx}(fg)" to the left-hand side:
"\\tfrac{d}{dx}(\\tfrac{dy(x)}{dx}(x+1)(2x+1))+\\tfrac{d}{dx}(2xy(x))-\\tfrac{d}{dx}((2x+2(x+1)+1)y(x))=(2x+1)^2"
5-step: Factor:
"\\tfrac{d}{dx}(\\tfrac{dy(x)}{dx}(x+1)(2x+1)+2xy(x)-(2x+2(x+1)+1)y(x))=(2x+1)^2"
6-step: Integrate both sides with respect to x:
"\\int\\tfrac{d}{dx}(\\tfrac{dy(x)}{dx}(x+1)(2x+1)+2xy(x)-(2x+2(x+1)+1)y(x))dx=\\int(2x+1)^2dx"
7-step: Evalute the integrals:
"\\tfrac{dy(x)}{dx}(x+1)(2x+1)+2xy(x)-(2x+2(x+1)+1)y(x)=\\tfrac{4x^3}{3}+2x^3+x+" C1
where C1 is an arbitrary constant.
8-step: Rewrite the equation:
"\\tfrac{dy(x)}{dx}+\\tfrac{-2(x+1)-1)y(x)}{(x+1)(2x+1)}=\\tfrac{-\\tfrac{4x^3}{3}-2x^3-x-C}{(x+1)(2x+1)}"
9-step: Let "\\mu(x)=exp(\\int\\tfrac{-2(x+1)-1}{(x+1)(2x+1)}dx)= \\tfrac{x+1}{(2x+1)^2}"
Multiply both sides by "\\mu(x):"
"\\tfrac{(x+1)\\tfrac{dy(x)}{dx}}{(2x+1)^2}+\\tfrac{(-2(x+1)-1)y(x)}{(2x+1)^3}=-\\tfrac{-\\tfrac{4x^3}{3}-2x^3-x-C}{(2x+1)^3}"
10-step: Substitute "\\tfrac{-2(x+1)-1}{(2x+1)^3}=\\tfrac{d}{dx}(\\tfrac{x+1}{(2x+1)^2}):"
"\\tfrac{(x+1)\\tfrac{dy(x)}{dx}}{(2x+1)^2}+\\tfrac{d}{dx}(\\tfrac{x+1}{(2x+1)^2})y(x)=-\\tfrac{-\\tfrac{4x^3}{3}-2x^3-x-C}{(2x+1)^3}"
11-step: Apply the reverse product rule "f\\tfrac{dg}{dx}+g\\tfrac{df}{dx}=\\tfrac{d}{dx}(fg)" to the ledt-hand side:
"\\tfrac{d}{dx}( \\tfrac{(x+1)y(x)}{(2x+1)^2}= -\\tfrac{-\\tfrac{4x^3}{3}-2x^3-x-C}{(2x+1)^3}"
12-step: Integrate both sides with respect to x:
"\\int\\tfrac{d}{dx}(\\tfrac{(x+1)y(x)}{(2x+1)^2})dx=\\int-\\tfrac{-\\tfrac{4x^3}{3}-2x^3-x-C_{1}}{(2x+1)^3} dx"
13 - step: Evaluate the integrals:
"\\tfrac{(x+1)y(x)}{(2x+1)^2}=\\tfrac{1}{3}(\\tfrac{1}{4}(2x+1)+\\tfrac{-6C_{1}+1}{8(2x+1)^2})+"C2
where C2 is an arbitrary constant.
14-step: Divide both sides by "\\mu(x)=\\tfrac{x+1}{(2x+1)^2}:"
"y(x)=\\tfrac{(2x+1)^2(\\tfrac{1}{12}(2x+1)+\\tfrac{-6C_{1}+1}{24(2x+1)^2}+C_{2})}{x+1}"
15-step: Simplify the arbitrary constants:
"y(x)=\\tfrac{(2x+1)^2(\\tfrac{1}{12}(2x+1)+\\tfrac{C_{1}}{(2x+1)^2}+C_{2})}{x+1}"
Comments
Leave a comment